The Relationship between Direct Language Learning Strategies and English Learning Proficiency at Senior High School Students - Rizal Arisman (J-SHMIC : Journal of English for Academic, 2020)
Learning strategies are applied by students to improve their studies. Suitable language learning strategies result in proficiency which is improved and greater self-confidence. Most researches observe the language learning strategies without dividing which affect more between direct and indirect strategy toward learning proficiency. Therefore, this research was conducted to find out whether the direct language learning strategies had a positive relationship and significant effect toward English learning proficiency on senior high school students. An ex-post-facto method with a correlational design was applied in this research. The population was 410 students at the eleventh grade of SMA Negeri 1 Baubau and selected 75 students as the sample using a simple random sampling technique. The instruments used were the SILL (Strategy Inventory for Language Learning) and the English proficiency test. The results of descriptive statistics indicate the compensation strategies were the most dominant learning strategy used by the eleventh-grade students with the mean score was 2.66. From the result of hypothesis testing, it was obtained the positive relationships and significant effect of those three kinds of strategies toward English proficiency on the eleventh-grade students. Besides, the memory strategies have the highest correction with the score of correlation is 0.756.